STUDY OF TECHNOLOGY OF GLAZED POTTERY FROM AN EXCAVATION IN THESSALONIKI, GREECE - Σοφιανοπούλου, Α.; Λαμπρόπουλος, Β.; Καντηράνης, Ν. (Bulletin of the Geological Society of Greece, 2004)
Samples of seven shells from vessels of glazed pottery of Palaeologan and post Byzantine period that were found during saving excavation of the 9th Ephoreia of Byzantine Antiquities in the centre of Thessaloniki, were studied with the methods of PXRD and SEM-EDS in order to investigate their firing conditions. Each shell is separated in three layers: the biscuit, the slip and the glaze. Biscuit constituted mainly of quartz, feldspars and muscovite, while the slip from quartz, feldspars, Pb-rich phase and muscovite. The glaze is constituted mainly by the Pb-rich phase that was recognized in the slip, quartz and feldspars. Amorphous phase was determined in all samples with increased percentages from biscuit to glaze. The EDS study confirms most of the results of PXRD study and shows, particularly in the glaze, the presence of very high percentages of PbO. The presence of Pb-rich phase in glaze constitutes an evidence for the temperature of second firing of glazed pottery and we believe that this temperature varied between 650 and 750 °C. Relatively to the maintenance of the studied glazed ceramics is recommended the reject of chemicals that solvating and dissolving the lead (e.g. EDTA, ethyl alcohol). The use of these chemicals can be cause weakening and destruction of enamelling and accordingly alteration of exterior layer of vessel.